MASJID, MODERASI BERAGAMA DAN HARMONI DI KOTA MEDAN - Fatimah Zuhrah; Yumasdaleni (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2021)
The sect of group and movement of radicalism, intolerance and violent extremism have emerged in the last decades in various parts of Indonesia as concern in the issue of religious moderation. The religious moderation discourse initiated by the Ministry of Religion in 2019 as mainstream target in anticipating the group who acts of violence in the name of religion. The city of Medan in North Sumatra, which has long been inhabited by people with diverse backgrounds of religions, ethnicities, cultures and languages, they can live together in a pluralistic way. This article discusses the role of mosques in maintaining harmony in plurality and tolerance in diversity. By using a qualitative methodology, through interviews and observations, this article presents several findings the role of mosques in maintaining religious moderation in Medan City. The data from four mosques as the location and place of informan object study. The result of the research first, the role of the Al-Mashun mosque in conveying of tolerance in social life has existed since was founded in 1909 (the era of the Deli sultanate). Second, the historical heritage became the next basic capital in preaching in several other mosques. The views and practices of da'wah are a) Tolerance in following various sect of thought even though the Shafi'i sect as mainstream. b) Different Islamic organizations as member and followers such as: Muhammadiyah, NU, Al-Washliyah etc. c) Dakwah content material is able to adapt in Islamic modern view. d) Dakwah concept of